Global Solutions, International Partnerships The European Investment Bank Development Report 2021 - European Investment Bank (European Investment Bank, 2021)
The climate crisis and the COVID-19 pandemic remind us that we cannot face down our challenges alone-our solutions must be global. The European Investment Bank is at the heart of the push to turn EU policy initiatives into real development solutions on the ground. This report provides insights into our vital projects and initiatives outside the European Union, data on their impact and ideas for the future of development through a series of expert essays.